The Role of the Endocannabinoid System in Oncology and the Potential Use of Cannabis Derivatives for Cancer Management in Companion Animals - Giorgia della Rocca; Alessandra Di Salvo; Erica Salucci; Michela Amadori; Giovanni Re; Cristina Vercelli (Animals)
The last decades of research have shown that the endocannabinoid system may be a promising therapeutic target for the pharmacological treatment of cancer in human medicine and possibly in veterinary medicine as well. Compared with the original cells, the expression of gene encoding for receptors and enzymes belonging to the endocannabinoid system has been found to be altered in several tumor types; it has been hypothesized that this aberrant expression may be related to the course of the neoplasm as well as to the patient’s prognosis. Several studies, conducted both in vitro and in vivo, suggest that both endo- and phytocannabinoids can modulate signaling pathways, controlling cell proliferation and survival. In the complex process of carcinogenesis, cannabinoids seem to intervene at different levels by stimulating cell death, inhibiting the processes of angiogenesis and metastasis, and regulating antitumor immunity. Although the molecular mechanisms by which cannabinoids act are not always clear and defined, their synergistic activity with the most used antineoplastic drugs in clinical oncology is showing promising results, thus providing veterinary medicine with alternative therapeutic targets in disease control. This review aims to summarize current knowledge on the potential role of the endocannabinoid system and exogenous cannabinoids in oncology, with specific reference to the molecular mechanisms by which cannabinoids may exert antitumor activity. Additionally, it explores the potential synergy between cannabinoids and conventional anticancer drugs and considers their application in veterinary oncology.